Dose Escalation Study of Concurrent Chemoradiotherapy With the Use of Involved-field Conformal Radiotherapy and Accelerated Hyperfractionation in Combination With Cisplatin and Vinorelbine Chemotherapy for Stage III Non–small Cell Lung Cancer: The Final Report. (October 2018) - Yoshimura, Naruo; Tada, Takuhito; Matsumoto, Yoshiya; Sawa, Kenji; Yoshimoto, Naoki; Suzumura, Tomohiro; Tanaka, Hidenori; Mitsuoka, Shigeki; Kimura, Tatsuo; Tamiya, Tomohiro; Hirashima, Tomonori; Kawaguchi, Tomoya; et al.
Abstract : Objectives: A phase I study to determine a recommended dose of thoracic radiotherapy using accelerated hyperfractionation for unresectable non–small cell lung cancer was conducted. Materials and Methods: We used chemotherapy of a cisplatin doublet and 2 dose levels of radiation with accelerated hyperfractionation. The radiation dose levels were: a total dose of 60 Gy in 40 fractions at level 1, and 66 Gy in 44 fractions at level 2. Eligible patients with unresectable stage III non–small cell lung cancer received cisplatin and vinorelbine. Radiation therapy started on day 2 of chemotherapy and was delivered twice daily for 5 days a week. Results: Total 12 patients were enrolled, with 6 patients each at dose levels 1 and 2. Dose-limiting toxicity was noted in 2 patients at level 1; one patient had grade 3 febrile neutropenia and the other patient had grade 3 esophagitis. No dose-limiting toxicity was noted in the 6 patients at level 2. Grade 3 to 4 leukopenia, neutropenia, and anemia were noted in 11 (92%), 9 (75%), and 8 (67%) of the total 12 patients, respectively. Grade 3 anorexia and infection were noted in 2 patients (17%) at each level. Grade 3 nausea, fatigue, esophagitis, and febrile neutropenia were noted in 1 patient (8%) at each level. The response rate in the total 12 patients was 83.3%. The median progression-free survival time and the median overall survival time were 10.7 and 24.2 months, respectively. Conclusions: Sixty-six gray in 44 fractions is the recommended dose for the following phase II study.